The relationship between job stress, imbalance, supervisor support, ambiguity, distributive fairness on burnout among public administrators / Mira Maisarah Sulaiman - Sulaiman, Mira Maisarah (Faculty of Business and Management, 2017)
Burnout can be characterized by depersonalization, emotional exhaustion, and reduced feelings of personal accomplishment which is a psychological response to work stress. Besides, burnout also may affect individuals in many of ways within the work setting in organization. Burnout consequences may be emotional, physical or intellectual. Furthermore, a report by HSE in 2016 has provide evidence that employees who works as public administrator in UK was reported to suffer high level of work related stress and burnout which is 48% from 79,000 cases of self reported work-related illness suffer in stress, depression or anxiety. Thus, literature highlighted many factors that contribute to burnout. This research was aimed to determine the relationship between job stress, imbalance, supervisor support, distributive fairness and burnout among public administrator in Majlis Perbandaran Johor Bahru Tengah Municipal Council. The population of this study is among public administrator. The questionnaires were distributed personally to 190 public servants in Perbandaran Johor Bahru Tengah Municipal Council. Only 172 respondents who are answering the question. The data from respondents is analyze using SPSS statistical software. Finding shows there is positive relationship between job stress, imbalance, and burnout. Meanwhile, supervisor support, distributive fairness and burnout have negative relationship. However, only supervisor support and distributive fairness is significant